2022
DOI: 10.3389/fcell.2022.854721
|View full text |Cite
|
Sign up to set email alerts
|

Density-Dependent Migration Characteristics of Cancer Cells Driven by Pseudopod Interaction

Abstract: The ability of cancer cells to invade neighboring tissue from primary tumors is an important determinant of metastatic behavior. Quantification of cell migration characteristics such as migration speed and persistence helps to understand the requirements for such invasiveness. One factor that may influence invasion is how local tumor cell density shapes cell migration characteristics, which we here investigate with a combined experimental and computational modeling approach. First, we generated and analyzed ti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 100 publications
(149 reference statements)
0
4
0
Order By: Relevance
“…When taking viable cell counts using flow cytometry, data for each cell line were gated based on the measured mean diameter of the cell ± three standard deviations of the mean based on a sample size of n = 5 from experimentation during device validation. Diameters for MDA-MB-231 and HCC38 cells were further validated by comparison to previous studies [ 22 , 23 ], but reliable previous data for MCF-12 cells could not be found.…”
Section: Methodsmentioning
confidence: 87%
“…When taking viable cell counts using flow cytometry, data for each cell line were gated based on the measured mean diameter of the cell ± three standard deviations of the mean based on a sample size of n = 5 from experimentation during device validation. Diameters for MDA-MB-231 and HCC38 cells were further validated by comparison to previous studies [ 22 , 23 ], but reliable previous data for MCF-12 cells could not be found.…”
Section: Methodsmentioning
confidence: 87%
“…This hybrid model can be utilized to investigate various aspects of the interplay between cells and the extracellular matrix in both singlecell and multicellular contexts. Possible extensions include the study of cell migration along fibers by using one of the many active cell migration models implemented for the CPM such as a polarity vector (Burger et al, 2022), or the Act model (Niculescu et al, 2015); the difficulty lies in the detachment of FAs at the rear of the migrating cell, this could be done, for example, by applying a model for asymmetric traction forces that would rupture the rear FAs or by introducing a chemical symmetry breaking component (Yamaguchi and Knaut, 2022). Another example of possible further study is that of multicellular mechanical interaction.…”
Section: Discussionmentioning
confidence: 99%
“…Would they adopt a different pattern in the same environment when fighting a more prevalent pathogen, or would they maintain the same migration mode even when it is no longer beneficial? We therefore suggest using models like the CPM [31, 13, 39, 40], where migration patterns arise naturally from an interaction between the cell and its environment rather than being imposed, to define the baseline expectations for T-cell search. By investigating which migratory characteristics emerge without being optimal or even beneficial, we can zoom in on the motility aspects that have truly been evolved to assist immune system function—without being misled by features that are merely inevitable side effects of an intracellular machinery acting in a complex environment.…”
Section: Discussionmentioning
confidence: 99%